Constitutional and Legal Landscape of Right to Be Forgotten in India - Sharma, Manoj Kumar; Kaur, Prabhjot (Lentera Hukum, 2025)
The right to be forgotten has emerged as an important right in the internet era, where on one hand information multiplies almost every day and on the other hand, the information appears to be preserved eternally. The presence of huge amounts of information in the public domain, particularly personal information, raises concerns about privacy in the digital era where sensitive information is often retained in the public domain, at times without consent of the data holder. When examined from the perspective of criminology and penology, the availability of information in the public domain about the past behavior of people adversely affects the chances of rehabilitation and reformation due to societal taboos. This raises an important question as to why one should suffer because of their past acts, thus underscoring the importance of the right to be forgotten. This paper traces the evolution and contours of the right to be forgotten in the European Union, the UK, the USA, and India, highlighting challenges in its implementation and recognition. The constitutional and legislative measures to recognize and enforce this right have also been examined in the light of judicial decisions. Keywords: Right to be Forgotten (RTF), Right to Privacy, Court, Constitution, Data.